Effect of dalargin on the content of goblet cells and mucins in the colonic mucosa in experimental ulcerative colitis - A. Yu. Liashev; G. S. Mal; A. V. Solin (Бюллетень сибирской медицины, 2024)
Aim. To investigate the protective effect of dalargin on the content of goblet cells and mucins in the colonic mucosa in a mouse model of ulcerative colitis.Materials and methods. Ulcerative colitis was simulated in Balb/C mice by replacing drinking water with 5% sodium dextran sulfate in boiled water for 5 days. Dalargin was administered subcutaneously in a volume of 0.1 ml at a dose of 100 μg / kg of body weight once a day for 7 days from the beginning of ulcerative colitis simulation. Sulfasalazine as a reference-listed drug was administered intragastrically at a dose of 200 mg / kg once a day for 7 days. The mice were sacrificed on day 5, 7, and 28. The sections of the distal colon were prepared and stained with hematoxylin and eosin, alcian blue (pH = 1.0) according to Mowry or by PAS reaction. In the sections, the number of goblet cells and acid and neutral mucins was determined.Results. In the mouse model of ulcerative colitis, the number of goblet cells (mainly at the bottom of the crypts), acid and neutral mucins decreased. Dalargin administration increased the number of goblet cells and the content of acid and neutral mucins in the colonic mucosa more effectively than sulfasalazine.Conclusion. Dalargin has a protective effect in ulcerative colitis.